2020
DOI: 10.2174/1567205017666200303141920
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Atherosclerotic Stenosis is Related to Post-stroke Cognitive Impairment: A Cross-sectional Study of Minor Stroke

Abstract: Background: Intracranial Atherosclerotic Stenosis (ICAS) is an important risk factor for cognitive impairment. However, it is unclear whether patients with ICAS are more likely to develop cognitive impairment after an acute, non-disabling ischemic stroke (minor stroke). Objective: We aimed to investigate the association between ICAS and post-stroke cognitive impairment. Methods: In this cross-sectional study, patients with acute, non-disabling ischemic stroke underwent two cognitive tests and imaging evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Moreover, we found that carotid calcification, artery stenosis and soft plaque density each had different effects on performance in each cognitive domain. In agreement with others studies, carotid artery stenosis and soft plaque density were significantly associated with impaired execution and visuospatial function ( Bos et al, 2012 ; Gong et al, 2020 ). These associations could be explained by the disruption of anterior and posterior watershed areas caused by hypoperfusion.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we found that carotid calcification, artery stenosis and soft plaque density each had different effects on performance in each cognitive domain. In agreement with others studies, carotid artery stenosis and soft plaque density were significantly associated with impaired execution and visuospatial function ( Bos et al, 2012 ; Gong et al, 2020 ). These associations could be explained by the disruption of anterior and posterior watershed areas caused by hypoperfusion.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with existing findings, demographic variables (age, sex, years of education) played important roles in predicting PSCI (Ojala-Oksala et al, 2012;Gong et al, 2020). In addition, imaging variables are corroborated by the existing literature identified as being important risk factors for PSCI.…”
Section: Discussionsupporting
confidence: 83%
“…First, repeated evaluation of cognitive status by MoCA scale within relatively short time, such as 3 months, may be affected by the learning effect, which commonly results in false negative outcome. Second, our previous finding shows incidence of PSCI at acute phase has reached a high level (>50%) (Gong et al, 2020). Therefore, we chose the 6 to 12 months as time point to evaluate PSCI for consideration that the cognitive condition of survivors may be in a relatively stable status during this time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations